2020
DOI: 10.1002/ange.201913825
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of 3‐Substituted Cyclobutenes by Catalytic Conjugate Addition/Trapping Strategies

Abstract: Ac opper-catalyzed tandem process to generate chiral cyclobutene derivatives has been developed. It is based on an enantioselective conjugate addition or reduction of ac yclobutenone and sequential trapping with ac hlorophosphate in aone-pot process.These phosphates are stable under mildly acidic conditions and serve as good electrophiles in Negishi coupling reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The Lu group recently reported copper‐catalyzed asymmetric additions to 3‐substituted cyclobutenones which allowed a variety of enantioenriched cyclobutenes to be obtained by trapping chiral intermediates with a suitable electrophile (Figure 2A). [18] …”
Section: Figurementioning
confidence: 99%
“…The Lu group recently reported copper‐catalyzed asymmetric additions to 3‐substituted cyclobutenones which allowed a variety of enantioenriched cyclobutenes to be obtained by trapping chiral intermediates with a suitable electrophile (Figure 2A). [18] …”
Section: Figurementioning
confidence: 99%
“…As a part of their ongoing effort to construct enantioenriched cyclobutanes, Lu and co-workers envisioned that the 1,4-addition/trapping reaction of 3-substituted cyclobutenones may offer a direct route to 3,3-disubstituted cyclobutene derivatives (Scheme 46). 53 It was found that using the phosphoramidite ligand 165 coordinated Cu(II) complex as the catalyst, dialkyl zinc could react with 3-substituted cyclobutenones 163 to give a chiral metal enol intermediate, which was then in situ trapped by diphenyl chlorophosphate to furnish chiral 3,3-disubstituted cyclobutene derivatives 164 in 46-78% yields and with 65-99% ee values.…”
Section: Asymmetric Alkylation and Miscellaneousmentioning
confidence: 99%
“…Examples of [2+2] cycloaddition, [ 4 ] ring expansion of cyclopropanes [ 5 ] and intramolecular ring closure of linear substrates [ 6 ] provide efficient routes to access chiral cyclobutanes. Another attractive alternative is the asymmetric post‐functionalization of prochiral cyclobutane derivatives, usually accomplished by α‐functionalization of cyclobutanones, [ 7 ] conjugate addition of cyclobutenones, [ 8 ] allylic alkylation of cyclobutenecarboxylic acid esters [ 9 ] and C—H functionalization [ 10 ] of cyclobutanecarboxamides. These protocols could expedite the diversification of cyclobutane‐tethered bioactive compounds.…”
Section: Background and Originality Contentmentioning
confidence: 99%